PERSEPSI HUKUM ISLAM TERHADAP SISTEM KEWARISAN BERBASIS BUDAYA PADA MASYARAKAT BUGIS BONE - Muh. Sabri (Institut Agama Islam Negeri Bone, 2021)
Abstract This research is the perception of the Islamic law Of Inheritance Based on the Culture of the community of Bugis Bone. Principal problem is social cultural society description of Bugis Bone, forms of inheritance system at Bugis society Bone and perceptions of Islamic law of inheritance based on the culture of the community of Bugis Bone. The results showed that the Social Cultural Community of Bugis Bone in daily life are bound by a system of norms and customary rules that are sacred and sacred in its entirety is called Pangadereng. For the community of Bugis in the Division of their heritage trust mallempa orowane, mancujung makunraie (male bear, while women carry). The specialty Division of inheritance system this is the home of heritage parents belong to the youngest, because he was with his parents until his parents died. This is because society has a culture of Bugis sibaliperri' (that) within the brotherhood, even for the people of Bugis male got a balanced heritage portion because he got home or the gold value is not less than that obtained by the male. Division of property in indigenous heritage considered to be mistaken in respect of the law of inheritance in Islamic jurisprudence. However, essentially Islamic law also received other legal norms that have grown and flourished as the norms and customs of indigenous communities, and distinctively custom it brings the benefit of the order, as well as harmony in the life of society, as long as it does not conflict with the norms of Islamic law itself.